2015
DOI: 10.1177/1461355715580912
|View full text |Cite
|
Sign up to set email alerts
|

Organisational challenges to delivering child investigative interviewer training via e-learning

Abstract: This article examined organisational challenges arising from the implementation of a new training course for investigative interviewers of vulnerable witnesses. The course was delivered via e-learning (computer exercises) and also involved mock interviews conducted over the telephone. Thematic analysis was conducted of: (a) trainees' anonymous written feedback submitted to an online discussion forum on the training programme's website, (b) trainees' responses to face-to-face questions during semi-structured qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…The participants were given online training in choosing effective questions, and engaged in simulated interviews with a virtual avatar several times a week. Results revealed enhanced interview quality posttraining [7,9,39]. Interview training with avatars in combination with providing trainees with regular feedback also improved interview quality [28,38].…”
Section: Interview Teachingmentioning
confidence: 93%
See 2 more Smart Citations
“…The participants were given online training in choosing effective questions, and engaged in simulated interviews with a virtual avatar several times a week. Results revealed enhanced interview quality posttraining [7,9,39]. Interview training with avatars in combination with providing trainees with regular feedback also improved interview quality [28,38].…”
Section: Interview Teachingmentioning
confidence: 93%
“…To be effective, training must include several features: it must occur over time, learned skills must be practices in context, and trainees must receive prompt, individual feedback over time [7,17]. Classroom training cannot easily provide all these features in ways that are both affordable and accessible to those requiring training, who are often working full-time and have complicated schedules.…”
Section: Interview Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although nine hours of refresher over a six-month period was perceived to be time-intensive for the police officers and their organizations (Anonymous et al, under review), our results suggested that it was not sufficient to significantly impact many dimensions of forensic interviews, at least among the present sample. The complexity of forensic interviews with children imposes a wide range of potential feedback on both the structure of the interview, the types of questions asked, the quality of the relationship with the child and the support provided, and the forensically relevant information obtained (Benson & Powell, 2015b, Powell, 2013Powell et al, 2016).…”
Section: Implications For Policy and Conclusionmentioning
confidence: 99%
“…The break was introduced to the SIM guidance in an attempt to keep interviews as brief as possible. Excessive questioning has been a consistent concern across a range of interviewer groups including police (Benson & Powell, 2015b; Westera et al, 2017), educators (Brubacher, Powell, Skouteris, & Guadagno, 2014) and lawyers (Powell, Westera, Goodman‐Delahunty, & Pichler, 2016). In relation to child interviews about abuse, a positive relationship has been found between the total number of questions asked by the investigative interviewer and the number of inconsistencies raised during cross‐examination (Pichler, Sharman, Powell, Westera, & Goodman‐Delahunty, 2019).…”
Section: Research Underlying the Core Phases And Variants Of The Simmentioning
confidence: 99%